DESKRIPSI KREATIVITAS MATEMATIKA DALAM PEMBELAJARAN BERBASIS MASALAH DENGAN PENDEKATAN OPEN ENDED - Sitti Busyrah Muchsin; Zam Immawan Alam; Ahmad Budi Sutrisno; Widya Salsabillah; Herman Alimuddin (HISTOGRAM: Jurnal Pendidikan Matematika, 2021)
This research is qualitative descriptive research, which aims to describe: (1) student creativity in product aspects, (2) student creativity in process aspects, (3) student creativity in affective aspects. The data collection techniques in this study are, the provision of mathematical problem-solving tasks (TPM), and task-based interviews in a blended (online and offline). Furthermore, the data will be analyzed qualitatively which includes: (1) the triangulation of data aimed at obtaining valid data. Triangulation used is triangulation method, which is comparing data through interviews with the results of student work, (2) doing reduction, abstraction, exposing data, (3) interpreting data, (4) concluding. The results showed that one subject from a high level based on GPA was able to show all indicators of creative thinking ability well, namely fluency, flexibility, novelty and elaboration in solving problems and can be classified into level 3 (Creative). One other subject from a high level based on GPA was able to show 2 indicators of creative thinking ability, namely fluency and elaboration in solving problems so that they can be classified into level 2 (Quite creative). While two subjects from the moderate level and two subjects from a low level based on GPA are only able to show one indicator of creative thinking ability, namely the elaboration indicator so that it can be classified into level 2 (Quite Creative).